Mediating Role of Interdependent Self-construal on Cultural Norms and Interaction Goals between Chinese and Malaysian Business Negotiators - Soo, Hoo Pin Lick; Abu Bakar, Hassan (2018)
China and Malaysia have been in bilateral relationship more than four decades. It was reported that China-Malaysia relations have developed rapidly in different areas which has increasingly matured and stable for the past four years (Thestar Newspaper, 28 August 2017). The mutual trust of shared opportunities is the main cause of a strong relationship regardless in diplomatic relations or business. Based on a study on Malaysian and Chinese business negotiators, we examine the total, direct and indirect effect of interdependent self-construal with cultural norms and interaction goals. It was found that in international business negotiations, business associates are influenced by interdependent selfconstrual, mediated the relation between cultural norms and interaction goals. The consequences of these findings are discussed and elaborated in this article.